Impact of Perioperative Brain Injury and Development on Feeding Modality in Infants With Single Ventricle Heart Disease - Anyir Hsieh; Sarah Tabbutt; Duan Xu; A. James Barkovich; Steven Miller; Patrick McQuillen; Shabnam Peyvandi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Tube‐assisted feeding in infancy is common in patients with single‐ventricle physiology (SVP). Postnatal brain development is delayed, and injury is common, in patients with SVP. The role of brain findings in feeding outcomes remains unclear. We sought to determine the association between neonatal perioperative brain injury and postnatal brain maturation with feeding‐tube dependency in patients with SVP at neonatal discharge and just before the stage‐2 palliation. Methods and Results We evaluated a cohort of 48 term neonates with SVP who underwent pre‐ and postoperative brain magnetic resonance imaging. Perioperative brain injury and microstructural brain development were measured with diffusion tensor imaging including fractional anisotropy in white matter and apparent diffusion coefficient in gray matter. The primary outcome was defined as being 100% orally fed (binary). Of the patients 79% (38/48) were tube fed at hospital discharge, and 27% (12/45) were tube fed before stage‐2 palliation. Perioperative brain injury did not differ by group. Orally fed patients had a faster rate of decrease in apparent diffusion coefficient (3%, 95% CI 1.7% to 4.6%, P<0.001) at discharge and a faster rate of increase in fractional anisotropy (1.4%, 95% CI 0.6% to 2.2%, P=0.001) at the time of stage‐2 palliation compared with tube‐fed patients, denoting more robust brain development. Conclusions Slower rate of postnatal brain maturation but not perioperative brain injury is associated with feeding modality in infancy. These results support the importance of brain health in optimizing feeding outcomes in patients with SVP.